CP-107 Use of botulinum toxin type A in esophageal achalasia: a case report. (24th February 2014) - Montserrat, M; Rizo, A; Lloret, A; Bayarri, C
Abstract : Background: In patients with oesophageal achalasia, pneumatic dilation is the treatment of choice, but it bears the risk of perforation in about 4% of cases. A new nonsurgical method, intrasphincteric injection of botulinum toxin A has shown promising initial results. Purpose: To evaluate clinical response following administration of botulinum toxin type A in a patient with oesophageal achalasia. Materials and methods: We report the case of an 85-year-old woman with oesophageal achalasia. The patient was admitted to our hospital for surgery for a fractured femur. During the rehabilitation period she developed progressive dysphagia to liquids and solids with regurgitation, needing parenteral nutrition. Gastroscopy was performed and showed oesophageal substenosis with normal-looking mucosa that was diagnosed as oesophageal achalasia. It was considered appropriate to administer botulinum toxin type A (Botox). Following current legislation regulating the off-label use of drugs (RD 1015/2009 and Instruction 05/ 2010 CatSalut), we required the patient's consent and the authorisation of the medical director. Results: A new gastroscopy was performed and 25 IU of botulinum toxin type A were injected in each oesophageal quadrant (total 100 IU). The patient started to eat normally again after 24 h with good tolerance. Conclusions: The endoscopy findings and good clinical response to botulinum toxin type A confirmed the first diagnosis as oesophageal achalasia. In this patient, botulinum toxin type A administration was very effective. Currently after 6 months, she persists without dysphagia and continues to eat normally. The results of several clinical trials show that botulinum toxin type A is effective in the treatment of dysphagia. In patients who are not candidates for aggressive treatments such as pneumatic dilation or surgical myotomy, especially in elderly patients, endoscopic intramucosal administration of botulinum toxin type A appears a good alternative. No conflict of interest.